Extracellular metabolomics of Trichoderma biocontroller for antifungal action to restrain Rhizoctonia solani Kuhn in cotton. (December 2020) - Gajera, H.P.; Hirpara, Darshna G.; Savaliya, Disha D.; Golakiya, B.A.
Abstract: The study evaluated antifungal action of Trichoderma biocontoller in opposition to cotton seed rotting pathogen Rhizoctonia solani . It perceived comparative appraisal of novel extracellular antifungal markers secreted by potent and weak antagonists to restrain R. solani contagion. The Trichoderma biocontroller exhibited growth restraint of R. solani Kuhn ranging from 15 to 88% during in-vitro antagonism. T. koningii MTCC796 (TkoniT9 ) controlled maximum growth of R. solani following T. viride NBAIITv23 (TviriT5 ) through mycoparasitism. The antibiosis strains- T. harzianum NBAIITh1 (TharzT1 ) and T. virens NBAIITvs12 (TvireT7 ) did not overgrow but formed inhibition zone during interaction with test-pathogen. The GC-MS analysis identified potentials secretory metabolites with 17 (including seven antifungal and antioxidant) and 13 (along with three antifungal) unique compounds in mycoparasitic TkoniT9 and TviriT5 strains, respectively. Metabolome univariate analysis of potent/weak group obtained 23 exometabolites with significant differences in fold change (threshold 2) between group, of which 16 up-regulated in potent antagonist group. The most diverse and potential markers for mycoparasitic action reported as 1-dodecene; 1-hexadecanesulfonyl chloride; phenol 3, 5-bis1, 1-dimethylethyl; 25H-furanone; octadecane and oxirane hexadecyl which were significantly up-regulated in mycoparasitic strains compared to the antibiosis and weak antagonists. However, oxirane dodecyl accounted unique for antibiosis action. The 1-nonadecene (antifungal) recognized significantly ( P 0.01 ) higher in antibiosis strain, while it's unique alcoholic form 1-nonadecenol (cytotoxic) induced significantly ( P 0.001 ) in mycoparasitic TkoniT9 antagonist contacted with pathogen mycelium. The novel exometabolites were documented for industrial use as potential markers in effective mycoparasitic and antibiosis Trichoderma strains for eco-friendly antifungal action against R. solani alternate to fungicides diminishing soil pollution in cotton rhizosphere. Graphical abstract: Image 1 Highlights: Antifungal novel bioactive constituents identified in potent antagonists by GC-MS profile. Metabolomics of two group (potent/weak) recognized 23 secretes with significant differences. Six novel potential markers obtained and significantly up regulated in mycoparasitic group. Cytotoxic 1-nonadecenol accounted most differential and unique for mycoparasitism. Antifungal oxirane dodecyl examined unique and potential marker for antibiosis action.